Molecular Insight into the Acryloyl-CoA Hydration by AcuH for Acrylate Detoxification in Dimethylsulfoniopropionate-Catabolizing Bacteria - Hai-Yan Cao; Peng Wang; Fei Xu; Ping-Yi Li; Bin-Bin Xie; Qi-Long Qin; Yu-Zhong Zhang; Yu-Zhong Zhang; Chun-Yang Li; Xiu-Lan Chen (Frontiers in Microbiology, 2017)
Microbial cleavage of dimethylsulfoniopropionate (DMSP) producing dimethyl sulfide (DMS) and acrylate is an important step in global sulfur cycling. Acrylate is toxic for cells, and thus should be metabolized effectively for detoxification. There are two proposed pathways for acrylate metabolism in DMSP-catabolizing bacteria, the AcuN-AcuK pathway and the PrpE-AcuI pathway. AcuH is an acryloyl-CoA hydratase in DMSP-catabolizing bacteria and can catalyze the hydration of toxic acryloyl-CoA to produce 3-hydroxypropionyl-CoA (3-HP-CoA) in both the AcuN-AcuK pathway and the side path of the PrpE-AcuI pathway. However, the structure and catalytic mechanism of AcuH remain unknown. Here, we cloned a putative acuH gene from Roseovarius nubinhibens ISM, a typical DMSP-catabolizing bacterium, and expressed it (RdAcuH) in Escherichia coli. The activity of RdAcuH toward acryloyl-CoA was detected by liquid chromatography-mass spectrometry (LC-MS), which suggests that RdAcuH is a functional acryloyl-CoA hydratase. Then we solved the crystal structure of RdAcuH. Each asymmetric unit in the crystal of RdAcuH contains a dimer of trimers and each RdAcuH monomer contains an N-terminal domain (NTD) and a C-terminal domain (CTD). There are three active centers in each trimer and each active center is located between the NTD of a subunit and the CTD of the neighboring subunit. Site-directed mutagenesis analysis indicates that two highly conserved glutamates, Glu112 and Glu132, in the active center are essential for catalysis. Based on our results and previous research, we analyzed the catalytic mechanism of AcuH to hydrate acryloyl-CoA, in which Glu132 acts as the catalytic base. This study sheds light on the mechanism of acrylate detoxification in DMSP-catabolizing bacteria.